Black Component of Dark Matter - A. V. Grobov; S. G. Rubin; V. Yu. Shalamova (Advances in High Energy Physics)
A mechanism of primordial black hole formation with specific mass spectrum is discussed. It is shown that these black holes could contribute to the energy density of dark matter. Our approach is elaborated in the framework of universal extra dimensions.